Pengaruh Beban Kerja Terhadap Kinerja Pegawai Biro Organisasi dan Tata Laksana Sekretariat Jenderal Kementerian Pertahanan Republik Indonesia - Salsabila Putri; Fitrotun Niswah; Meirinawati M; Eva Hany Fanida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Employee performance is one of the key indicators of a government organization's success in achieving its goals, therefore, workload must be managed proportionally to maintain optimal performance. Biro Ortala Setjen Kemhan RI shows indications of an increased workload due to human resource limitations, suboptimal task distribution, and inadequate workspace conditions. This study aims to analyze the effect of workload on employee performance at the Biro Ortala. This study employs a quantitative approach with an associative research design. Data were collected through questionnaires, interviews, and documentation, and then analyzed using simple linear regression via SPSS version 27. The results reveal that workload has a significant effect on employee performance at the Biro Ortala (Sig. 0.000 0.05), with a correlation coefficient of -0.714, indicating a strong and negative relationship. The coefficient of determination of 51% indicates the contribution of workload to the variation in employee performance, while other factors outside the model influence the remaining 49%. These findings reveal that an increase in the workload experienced by employees is followed by a decline in their performance, with mental and physical workload asthe dominant factors.